When Your Kind Cannot Live Here: How Generic Language and Criminal Sanctions Shape Social Categorization. (November 2017) - Goldfarb, Deborah; Lagattuta, Kristin Hansen; Kramer, Hannah J.; Kennedy, Katie; Tashjian, Sarah M.
Using generic language to describe groups (applying characteristics to entire categories) is ubiquitous and affects how children and adults categorize other people. Five-year-olds, 8-year-olds, and adults ( N = 190) learned about a novel social group that separated into two factions (citizens and noncitizens). Noncitizens were described in either generic or specific language. Later, the children and adults categorized individuals in two contexts: criminal (individuals labeled as noncitizens faced jail and deportation) and noncriminal (labeling had no consequences). Language genericity influenced decision making. Participants in the specific-language condition, but not those in the generic-language condition, reduced the rate at which they identified potential noncitizens when their judgments resulted in criminal penalties compared with when their judgments had no consequences. In addition, learning about noncitizens in specific language (vs. generic language) increased the amount of matching evidence participants needed to identify potential noncitizens (preponderance standard) and decreased participants' certainty in their judgments. Thus, generic language encourages children and adults to categorize individuals using a lower evidentiary standard regardless of negative consequences for presumed social-group membership.